2013
DOI: 10.1136/jech-2012-201465
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the UNREST questionnaire for testing the social resistance framework

Abstract: The preliminary results of our pilot study suggest that the new tool may be useful for testing the framework. The results also provide support for the framework in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…As can be seen from Table 1, all factor loadings are significant ( p < 0.001) and higher than the traditional threshold of 0.4 (Reisig et al 2007). The Cronbach α value for most scales is higher than the commonly used threshold of 0.7, which supports the reliability of the scales (DeVellis 2003; Factor, Kawachi, and Williams 2013a). The Cronbach’s α values of the “outcomes of the pandemic-policing” scale ( α = 0.61) and “broad societal concerns” scale ( α = 0.63) are somewhat lower, which is expected given that there are only two survey items in each of these scales (Keizer, Dykstra, and Jansen 2008).…”
Section: Methodssupporting
confidence: 62%
“…As can be seen from Table 1, all factor loadings are significant ( p < 0.001) and higher than the traditional threshold of 0.4 (Reisig et al 2007). The Cronbach α value for most scales is higher than the commonly used threshold of 0.7, which supports the reliability of the scales (DeVellis 2003; Factor, Kawachi, and Williams 2013a). The Cronbach’s α values of the “outcomes of the pandemic-policing” scale ( α = 0.61) and “broad societal concerns” scale ( α = 0.63) are somewhat lower, which is expected given that there are only two survey items in each of these scales (Keizer, Dykstra, and Jansen 2008).…”
Section: Methodssupporting
confidence: 62%
“…Participants also learned about the "UNREST" study, which showed that power relations within society may encourage members of minority groups to actively engage in acts of everyday resistance and that individuals who feel alienated from the larger society, regardless of the reason, may engage in high-risk behaviors as a mean of voicing their disaffection. 12 Facilitators and participants followed with dialogue about the negative effects of participation in high-risk behaviors on overall health.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was based on the UNREST and DRQ questionnaires, which have been previously validated (Factor, Kawachi, and Williams 2013a, Factor et al 2013b). In addition, the questionnaire included scales for estimating respondents’ obligation to obey the police and perceptions of procedural justice (Jackson et al 2011; Jonathan-Zamir and Weisburd 2011; Mehozay and Factor 2017; Tyler and Jackson 2014), self-help (vigilantism; Tankebe 2009) and anger (Spielberger et al 1985).…”
Section: Methodsmentioning
confidence: 99%